Moroccan Architectural Influences on Egyptian Religious Architecture in the Fatimid Period - صارم وفاء (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The Fatimid era in Egypt witnessed many developments, including architectural, as a result of the bestowal of the Caliphs money and their taste for civilization in general, and architecture in particular, and the Fatimids printed Egypt with different and different prints (effects), and these influences were a bright mix of Moroccan and Andalusian at times. Fatimid architecture, whether in Morocco and Egypt, is a cultural pillar to show the intellectual identity of the Fatimids. There are many ways for the transmission of Moroccan influences on Egypt, including the result of the existing military situation at the time, and what came peacefully. The Fatimids, after the consolidation of their state’s affairs in Morocco, prepared military campaigns to enter Egypt And trade helped to transfer influences between Morocco and Egypt, despite the multiple revolutions and unrest in Morocco, and this matter helped the stability of entire families in Egypt.. The third point is scientific trips of all kinds, which are an important source in history, and travelers depict and convey what he deems accurate. In addition to the Hijazi trips, which are a school in Egyptian history, they came for two things: Hajj and seeking knowledge. The Moroccan architectural influences revolve around Fatimid architecture, through which the Fatimids were keen to develop a cultural identity specific to their country that reflects the civilizational concept of their religious beliefs. Fatimid architecture has a specific style in the engineering designs of the facilities to be erected.